Telekardiologi dan Aplikasinya: Pendekatan Rumah Sakit selama Pandemi - Purwowiyoto, Sidhi Laksono; Achadi, Anhari; Wibowo, Adik (Sanus Medical Journal, 2021)
Covid19 has changed how we serve patients in all areas of health, and cardiology is no exception. Telemedicine is an option that hospitals can do during this pandemic. Telecardiology is part of telemedicine. By transmitting clinical data and electrocardiograms, telecardiology allows access to cardiology consultation services (telecardiology) without the need to travel to the practice area for both patients and cardiologists. These services can be in the form of teleconsultation, teleelectrocardiography, telerehabilitation, or teleechocardiography. Telecardiology can be applied in prehospital (teleconsultation, teleelectrocardiography,) if there is a referral for a heart attack patient or consult for chronic heart disease through online mediaÍ¾ at the hospital in the form of discussions with peripheral hospitals and referral hospitals (teleechocardiography with other small hospitals)Í¾ and posthospital treatment can be performed for cardiac telerehabilitation in patients with heart failure or teleconsultation of posttreatment patients.